2014
DOI: 10.3390/v6124811
|View full text |Cite
|
Sign up to set email alerts
|

Alpharetroviral Vectors: From a Cancer-Causing Agent to a Useful Tool for Human Gene Therapy

Abstract: Gene therapy using integrating retroviral vectors has proven its effectiveness in several clinical trials for the treatment of inherited diseases and cancer. However, vector-mediated adverse events related to insertional mutagenesis were also observed, emphasizing the need for safer therapeutic vectors. Paradoxically, alpharetroviruses, originally discovered as cancer-causing agents, have a more random and potentially safer integration pattern compared to gammaretro- and lentiviruses. In this review, we provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 152 publications
(193 reference statements)
0
22
0
7
Order By: Relevance
“…Ce tropisme contribue probablement à l'expression des RV [6][7][8][9] mais il explique aussi, en partie [10], leur oncogénicité marquée car il accroît impliquées dans la sélection des sites d'intégration. En effet, un LV hybride codant IN de MLV tend à reproduire la prédilection des RV pour l'intégration au sein des promoteurs [4].…”
Section: Profil D'intégration Et Oncogénicitéunclassified
See 3 more Smart Citations
“…Ce tropisme contribue probablement à l'expression des RV [6][7][8][9] mais il explique aussi, en partie [10], leur oncogénicité marquée car il accroît impliquées dans la sélection des sites d'intégration. En effet, un LV hybride codant IN de MLV tend à reproduire la prédilection des RV pour l'intégration au sein des promoteurs [4].…”
Section: Profil D'intégration Et Oncogénicitéunclassified
“…Pour comprendre comment IN de MLV sélectionne les sites d'intégration, trois équipes ont cherché les protéines cellulaires capables d'interagir avec elle. Les partenaires identifiés sont trois protéines apparentées, BRD2 (bromodomaincontaining protein 2), BRD3 et BRD4, qui présentent deux bromodomaines préférentiellement dans le corps des gènes transcrits ( Figure 1B) [2][3][4][6][7][8][9][10][11][12]. Les LV sont moins oncogéniques que les RV [10].…”
Section: Profil D'intégration Et Oncogénicitéunclassified
See 2 more Smart Citations
“…SIN HIV vectors have been used in human trials and have the advantage that they can effectively transfect resting cells due to their nuclear import properties [89,96] . Finally, SIN avian retrovirus vectors have been developed but have not been used in human gene therapy [97] . Consistent with the observation that avian retroviruses integrate randomly into cellular DNA [34,35] , genome-wide analysis of integration sites by a SIN avian retrovirus vector in human hematopoietic stem/progenitor cells demonstrated that integration is random and not near hotspots containing protooncogenes like LMO2 [98] .…”
Section: Human Gene Therapymentioning
confidence: 99%